Analisis Karakter Patih Udawa dalam Perspektif Ajaran Agama Islam - Arif Muzayin Shofwan Shofwan; Imam Karya Bakti; Fuad Ngainul Yaqin; Marwan Hayeemaming; Hana Athia Akhzalini (Universitas Islam Balitar, 2025)
Patih Udawa is a puppet character who is the son-in-law of Patih Sengkuni. If Patih Udawa has a positive character with several shortcomings, then Patih Sengkuni predominantly has a negative character. This qualitative research using literature study will analyze Patih Udawa's character from the perspective of Islamic religious teachings. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research resulted in the conclusion that Patih Udawa has several positive characteristics that are significant to the teachings of the Islamic religion as follows, among others: honest and significant to the QS. Al-Ahzab verse 70 and HR. Bukhari; obeying the orders of the king or leader (ulil amri) is significant with QS. An-Nisa verse 59; significant fidelity with QS. Al-Ahzab verse 23 and QS. An-Nahl verse 95; clever at adapting to circumstances in the sense of being filled with tenderness and significant affection with QS. Ali Imran verse 159 and HR. Muslim; and significant savvy with HR. Ahmad, HR. Bukhari, and HR. Turmudzi. One of Patih Udawa's shortcomings is his lack of skill in solving problems. Patih Udawa's incompetence in resolving significant problems with QS. Al-Ahzab verse 27 where humans always commit wrongdoing and are stupid towards themselves. However, Patih Udawa's lack of competence does not make him a completely negative character. This is different from the nature and character of his father-in-law, namely Patih Sengkuni, whose negative side is more dominant.